'Getting it right': an ethnographic study on how palliative care nurses discuss death. (6th May 2010) - Kovan, Lynne; De Vries, Kay
This study examines hospice nurses' perceptions of the needs of dying patients in relation to achieving a 'good death'. An ethnographical methodology was used to observe nurses during their handover reports. Findings revealed that hospice nurses strive to achieve the best possible care for their patients. The need to 'get it right' was a crucial component and encompassed the stories nurses told about the care of their patients. Akin to the patients' requirements was the emotional burden that caring for the dying had on the nurses, and how this was eased by the reflective nature of their handover discussions.